PENGARUH KOMUNIKASI, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMK - Edi Siregar; Akbar Prabowo (Jurnal Satya Mandiri Manajemen dan Bisnis, 2025)
This research aims to determine whether there is an influence of Communication, Work Environment and Work Discipline on Teacher Performance at Mutiara Bangsa Al-Huda Vocational School, West Jakarta, simultaneously or partially. The data used in this study are secondary data and primary data collected by distributing questionnaires to 50 teachers who were respondents. This research uses quantitative causality and the results of this research are based on respondents' answers using a Likert scale. The analytical methods used in this research are multiple linear regression test, F test (simultaneous), t test (partial), and coefficient of determination. The results of this research show that using the F test (simultaneous) there is a significant influence between Communication, Work Environment and Work Discipline on Teacher Performance. Meanwhile, the t test (partial) shows that communication has a positive and significant effect on teacher performance. The work environment has a significant positive effect on teacher performance. Work Discipline has a negative and significant effect on Teacher Performance. With a coefficient of determination value of 36.3%, which means that teacher performance can be explained by communication, work environment and work discipline and the remaining 63.7% is influenced by other variables not explained in this research.